1997
DOI: 10.1046/j.1365-3083.1997.d01-401.x
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Class II Region Confers Susceptibility to Staphylococcus aureus Arthritis

Abstract: The importance of the MHC class II region for the development of septic arthritis was studied in a murine model of haematogenously induced Staphylococcus aureus arthritis. In the first experiment MHC class II deficient mice (Ab ¹=¹ ) and their heterozygous (Ab þ=¹ ) littermates were intravenously inoculated with a single dose of toxic shock syndrome toxin-1 producing S. aureus LS-1 strain. The results demonstrate that the expression of class II MHC molecules increases the prevalence and severity of arthritis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…We have assessed whether mice that were isogeneic for the major histocompatibility complex (MHC) displayed different outcomes for staphylococcal arthritis. Our results indicated that this was indeed the case, since mice that expressed certain MHC haplotypes were better protected against the infection[28]. Such an outcome may be due to differential expansion capacity of certain T cell receptor families in response to staphylococcal superantigens depending on host MHC background[29].…”
Section: Non‐specific Innate Immune Responses To Invading Staphylococcisupporting
confidence: 52%
“…We have assessed whether mice that were isogeneic for the major histocompatibility complex (MHC) displayed different outcomes for staphylococcal arthritis. Our results indicated that this was indeed the case, since mice that expressed certain MHC haplotypes were better protected against the infection[28]. Such an outcome may be due to differential expansion capacity of certain T cell receptor families in response to staphylococcal superantigens depending on host MHC background[29].…”
Section: Non‐specific Innate Immune Responses To Invading Staphylococcisupporting
confidence: 52%
“…Animal models indicate that these bacteria are especially arthritogenic (Bremell and Tarkowski 1995). Using a similar model, MHC class 11 molecular expression were shown to increase the prevalence and severity of arthritis (Abdelnour et al 1997). N itric oxide is an important mechanism used by the macrophage for killing ingested bacteria.…”
Section: Pathophysiology Including Morphology Biochemistry Geneticmentioning
confidence: 97%
“…We have assessed whether mice that were isogeneic for the major histocompatibility complex (MHC) displayed di¡erent outcomes for staphylococcal arthritis. Our results indicated that this was indeed the case, since mice that expressed certain MHC haplotypes were better protected against the infection [28]. Such an outcome may be due to di¡erential expansion capacity of certain T cell receptor families in response to staphylococcal superantigens depending on host MHC background [29].…”
Section: Non-speci¢c Innate Immune Responses To Invading Staphylococcimentioning
confidence: 52%